The Man Who Knew God Decoding Jeremiah. - Schreiber, Mordecai (Lanham : Rowman & Littlefield Pub. Group, 2010)
The Man Who Knew God unravels the complexities of the book of Jeremiah and argues that this prophet is the key figure in shaping Western civilization. Mordecai Schreiber posits that Jeremiah is not only the one who eradicated paganism amongst the Hebrew people, but he can also be considered the founder of the post-biblical Jewish faith. Offering intriguing insight into Jeremiah's role in the founding of Western monotheism and the eradication of paganism amongst the Hebrew people, this book should beread by all those interested in Biblical studies, Jewish studies, and religion.
Preface; Note on the Translation of the Bible; Kingdom of Judah in the Time of Jeremiah; Timeline of Events in the Book of Jeremiah; Chronology of the Book of Jeremiah; Chapter One The Life and Mission of Jeremiah; Chapter Two The Jewish and the Universal Jeremiah; Chapter Three What Would Jeremiah Have to Say to Us Today?; NOTES; Bibliography; Index of Biblical Passages; Index; About the Author.
Description based on print version record.
Keywords: Bible. -- O.T. -- Jeremiah -- Criticism, interpretation, etc; Religion; Bible. -- Criticism, interpretation, etc; RELIGION / Biblical Studies / Prophets; Electronic books